(untitled) (Journal of Engineering, 2010)
Most prime movers have vibrational problems due to the inherent unbalance in the engines. The unbalance may be due to faulty design or poor manufacture. Naturally, the structures designed to support heavy centrifugal machines, like motors, turbines and reciprocating pumps, are also subjected to vibration. In all these situations, the structure or machine component subject to vibration can fail because of material fatigue resulting from the cyclic variation of the induced stress. Furthermore, the vibration causes more rapid wear of machine parts such as bearings and gears and also creates excessive noise.This research is an example in the field of reducing as much as possible the vibration. To accomplish this, a digital instrument, based on an industrial computer, designed to measure the vibration level and rotor speed. Thereafter, displaying the required amount of weight that must be added or removed from blade in order to reduce the unbalance, which cause vibration